Analysis of Application of Accounting Information Systems Receivable Billing In Increasing The Effectiveness of Cash Receiving In The Company - Nurawaliya Fairin Oktavianita; Siwidiyah Desi Lastianti; Yanna Eka Pratiwi; Ida Budiarti (Journal of Economy, Accounting and Management Science (JEAMS), 2022)
The objectives to be achieved in this study are to find out the extent of the accounting information system for collecting receivables in increasing the effectiveness of cash receipts implemented by PT. Karunia Indah Delapan Expres. The following actions were done to reach the aims of this study are: 1. perform an analysis of the accounting information system on the collection of receivables applied by PT. Karunia Indah Delapan Express, 2. Analyze the accounting information system for collection of accounts receivable to see if it can support the effectiveness of PT. Karunia Indah Delapan Expres, 3. Identify the problems and causes of problems that PT. Karunia Indah Delapan Expres is facing. From the results of the research and analysis carried out it can be concluded that:1. The slowness of the delivery letter to return to the original branch. 2. The lack of the number of collectors / collection officers of receivables. 3. The number of account numbers in PT. Karunia Indah Delapan Expres Surabaya.